High-performance sport, learning and culture: new horizons for sport pedagogues? - Penney, D.; McMahon, J. (Physical Education and Sport Pedagogy, 2016)
Background: Research in sport coaching and sport pedagogy including studies published in this special issue bring to the fore the relationship between learning and culture in contexts of high-performance sport. This paper acknowledged that how learning, culture and their relationship are conceptualised is a crucial issue for researchers and professionals in high-performance sport.